2024
DOI: 10.1371/journal.pone.0296830
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of privacy or structural violence? Harassment against women in public transport environments: A systematic review

Sergio A. Useche,
Natura Colomer,
Francisco Alonso
et al.

Abstract: Background Despite being neglected for several decades, and in many countries, public transport environments have transformed into a reflection of social disparities and inequalities. Among these issues, harassment–a pervasive and worldwide gendered dynamic–has been demonstrated to negatively impact women’s behavioral trends, daily opportunities, and health impacts, as well as safety and security outcomes. Aim This systematic review aimed to examine a set of studies analyzing harassment against women in publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…The perception of service quality also plays a significant role, including aspects such as cleanliness, safety, and overall travel experience [ 21 ]. In relation to safety, several studies have shown that it is a particularly relevant factor in women's choice of transport, with public transport vehicles and bus stops or stations being perceived as unsafe and more likely to suffer a situation of harassment or sexual aggression, especially at night [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The perception of service quality also plays a significant role, including aspects such as cleanliness, safety, and overall travel experience [ 21 ]. In relation to safety, several studies have shown that it is a particularly relevant factor in women's choice of transport, with public transport vehicles and bus stops or stations being perceived as unsafe and more likely to suffer a situation of harassment or sexual aggression, especially at night [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%